(untitled) (Education in the 21st Century, 2023)
It is known that deep and partial visual impairments significantly impede playing, cognitive, educational, labor and other types of human activity, physical culture and sports. Therefore, the study of the attitude of students with visual impairments to physical culture and sports will become the basis for the effective organization and conduct of educational work with these students in physical education, sports and recreation, correctional development and sports work. It has been established that a person’s attitude to a particular activity is formed on the basis of interests in them. This provision also applies to the attitude of students with visual impairments to physical culture and sports, to training sessions, morning exercises, independent physical exercises and sports in their free time. From the formation and development of interest in these and other types of physical education, the correct and effective organization and conduct of these events largely depend on the preservation of good health, physical development of the motoric and orientation in space for students with visual impairments. The joy received from physical exercises, from overcoming objective obstacles and one’s own weaknesses, contributes to the development of self-confidence, the development of such positive personality traits as purposefulness, diligence, achievement of the intended goal, etc. Therefore, many teachers emphasize the need to identify students’ interests, take into account and develop them in their daily work. However, in the scientific and methodological literature, insufficient attention is paid to the formation and development of interest and attitude of students with visual impairments to physical culture and sports. At the same time, a deep and versatile study of this problem, the invesigation of various approaches is very important, which determines the relevance of this study, its theoretical and practical significance. In connection with the above, the purpose of this study is to study the attitude of students with visual impairments to physical culture and sports. The article presents the results of a study of the attitude of 1-2 year students with visual impairments to physical education classes, morning exercises, to independent physical exercises in their free time and to sports. Based on the study of the results of the study, a theoretical analysis of the issues under consideration was carried out, conclusions and practical recommendations were drawn.